Foreign direct investment in the agricual sector in Iraq problems and solution - Naji Khalaf, Sahar (Iraqi Journal for Administrative Sciences, 2024)
Foreign direct investment plays an important role in economic development, increasing national income and operating manpower, and with a growing population, increased demand for consumer goods, and an increase in the import of food commodities due to the lack of local production and weak investments in this sector due to the political and economic conditions that the country is going through. The research concluded that Iraq is an investment-repellent country due to the lack of an appropriate investment climate represented in infrastructure such as roads and transportation, as well as water scarcity in recent years due to the lack of rain, political and security instability in the country. and the abundance of administrative and financial corruption.